Exploring the potential impact of group identity on post-traumatic growth in the aftermath of Corona outbreak: function of social–emotional competence as a mediator - Ma, Jinfu; Khan, Ahsan Riaz; Zhang, Hai-Jun; Jun, Zhang; Abonazel, Mohamed R.; Ahmad, Muhammad Salman; Tageldin, Elsayed M.; Alzahran, Ali Rashash R. (Frontiers in Public Health, 2023)
Background: This research endeavors to examine the potential effects of human and societal interactions on individuals' post-traumatic growth in the aftermath of the Corona outbreak. To achieve the aforementioned objective, the current research investigates the correlations between post-traumatic growth and group identity, while also examining the potential mediating function of social-emotional competence. Methods: A cross-sectional design included a representative sample of 2637 high school students located in the capital territory of Pakistan using convenience sampling method. To explore the associations, correlation and mediation analyses utilizing the group identification scale, the socialemotional competence scale, and the post-traumatic growth scale was performed with SPSS PROCESS 4 macro and AMOS. Results: The findings demonstrated that group identification emerged as a substantial predictor substantially associated with post-traumatic growth. Moreover, the relationship linking group identification and post-traumatic growth was found to be partially moderated by social-emotional competence.The phenomenon of group identification can exert influence on post-traumatic growth through both direct and mediating pathways, with the latter being essentially mediated by social-emotional competence. The aforementioned outcomes possess significant academic and practical implications concerning the promotion of post-traumatic growth and the improvement of psychological well-being after the Corona outbreak.